INFLUENCE OF AMENDED MELAMINE PHOSPHATE (AMP) AT DIFFERENT LEVELS OF FERTILIZER ON YIELD ATTRIBUTING CHARACTERS, YIELD AND NODULATION ON SOYBEAN OF CHHATTISGARH PLAIN - RAKESH KUMAR PATEL,; S. B. GUPTA,; ASHWANI KUMAR THAKUR,; PRAFULL KUMAR,; NITESH KUMAR GAWANDE, (The Bioscan, 2015)
The experiment was conducted under field conditions at Instructional cum Research Farm, IGKV, Raipur (Chhattisgarh) during kharif2011-12 to assess the effect of amended malanine phosphate (AMP) at variable levels of commercial fertilizers affecting grain yield in soybean. The experiment was laid out in trireplicated Randomized Block Design (RBD) with nine nutritional schedules. At 15 and 60DAS, Plant height (14.18 and 66.17 cm), number of pods/plant (34.12), grain yield (26.55 q/ha), straw yield (22.84 q/ha) and N uptake by nodules (13.96 mg/plant) were recorded significantly highest in treatment T2 (Rhizobium inoculation + 100% RDF). However, number of nodules/plant (80.00 per plant) was recorded significantly higher in T6 (Rhizobium inoculation + 75% RDF+amended melamine phosphate soil application) but fresh weight of nodules (0.825 g/plant), dry weight of nodule (0.187 g/plant) and N contain of nodules (6.89 mg/plant) were recorded significantly highest in T9 (Rhizobium inoculation + 75% RDF+amended melamine phosphate soil application+ foliar application).From the above study it can be concluded that combined application of Rhizobium inoculants along with amended melamine phosphateis suitable combination to increase soybean productivity inChhattisgarh plain.